Whole Genome Sequencing in the Undergraduate Classroom: Outcomes and Lessons from a Pilot Course - Jennifer C. Drew (American Society for Microbiology, 2008)
The BIO2010 report challenged undergraduate institutions to prepare the next generation of researchers for the changing direction of biology that increasingly integrates advanced technologies, digital information, and large-scale analyses. In response, the Microbiology and Cell Science Department at the University of Florida developed a research-based course, “Bacterial Genome Sequencing.” The objectives were to teach undergraduates about genomics and original research by sequencing a bacterial genome, to develop scientific communication skills by writing and submitting the project results as a class effort, and to promote an interest in biological research, particularly genomics. The students worked together to sequence, assemble, and annotate the Enterobacter cloacae P101 genome. We assessed student learning, scientific communication skills, and student attitudes by a variety of methods including exams, writing assignments, oral presentations, pre- and postcourse surveys, and a final exit survey. Assessment results demonstrate student learning gains and positive attitudes regarding the course.